Integration of Ethnoscience in High School Biology Learning: A Systematic Literature Review from 2021–2025 - Husni, Rafeah; Mukra, Rizal (Bioedunis Journal, 2025)
This study aims to analyze the development of studies on the integration of ethnoscience into biology learning in high schools during the 2021–2025 period. The method used was a systematic literature review (SLR) by searching articles through Google Scholar using keywords related to ethnoscience and biology education in high schools. A total of 30 articles met the inclusion and exclusion criteria and were analyzed through a process of identifying, reviewing, analyzing, and interpreting data. The results showed that the majority of studies focused on the development of ethnoscience-based learning tools (36.7%) and their implementation in the classroom (33.3%). In the domain of learning outcomes, the greatest improvement occurred in critical thinking skills (33.3%), followed by cognitive skills, scientific literacy, understanding of scientific concepts, and psychomotor skills. The material most frequently associated with local wisdom was biodiversity (29%). These findings confirm that ethnoscience is effective in strengthening conceptual understanding and higher-order thinking skills through a culturally relevant context.